Effects of Volume and Lighting Equipment Features on Lighting in An Open Plan Office: An Analysis - Celik, Kasim; Kucukkilic Ozcan, Esra; Unver, Rengin (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2015)
In today's spaces, there is a need for appropriate conditions in terms of elements of the physical environment, and also with respect to function and aesthetics. Conditions of comfort are important in order for the activities taking place in the space to be performed without any difficulty, fatigue or inefficiency. One such condition of comfort is lighting, an element of the physical environment. Any design of a lighting scheme and its quantity and quality should be based on the requirements of the scheme's users and their activities. In this context, not only the illumination itself but also its specifications, such as color, direction, distribution, changes in level and glare are important for preformation of activities. In a lighting design, luminance distribution and level depends on parameters such as location and illuminance intensity distributions, dimension of space and reflectivity of interior surfaces. This paper examines the case of an open plan office, and evaluates and analyzes the effects of the above-mentioned parameters on artificial illuminance levels, uniform distribution of illuminance, glare values and energy use in lighting schemes.
Keywords: Luminaire; uniform distribution of illuminance; open plan office; energy use; illuminance intensity distribution; glare; Architecture